The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fresc.2022.910068
|View full text |Cite
|
Sign up to set email alerts
|

IVIM Imaging of Paraspinal Muscles Following Moderate and High-Intensity Exercise in Healthy Individuals

Abstract: BackgroundQuantification of the magnitude and spatial distribution of muscle blood flow changes following exercise may improve our understanding of the effectiveness of various exercise prescriptions. Intravoxel incoherent motion (IVIM) magnetic resonance imaging (MRI) is a technique that quantifies molecular diffusion and microvascular blood flow, and has recently gained momentum as a method to evaluate a muscle's response to exercise. It has also been shown to predict responses to exercise-based physical the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Nevertheless, the variability and sensitivity of parameters needs to be taken into consideration when powering studies and interpreting results. Comparing these results to prior studies, there has been a wide range of IVIM parameters reported in muscle (8,9,35). This variability may in part be due to the lack of standardization of fitting approach, as results herein show significant differences in parameter values depending on choice of analysis method.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Nevertheless, the variability and sensitivity of parameters needs to be taken into consideration when powering studies and interpreting results. Comparing these results to prior studies, there has been a wide range of IVIM parameters reported in muscle (8,9,35). This variability may in part be due to the lack of standardization of fitting approach, as results herein show significant differences in parameter values depending on choice of analysis method.…”
Section: Discussionsupporting
confidence: 57%
“…employed in a variety of muscles, including those in the leg (1-4), shoulder (5,6), and lumbar spine (7)(8)(9). While ASL can quantify perfusion in physiologically relevant units, its spatial extent is somewhat limited and the perfusion response to stimuli such as exercise or induced ischemia dissipates quickly (10).…”
mentioning
confidence: 99%
“…For individuals in the exercise group, an acute pre‐operative machine‐based resistance exercise bout was performed on the day of surgery prior to pre‐operative check in. Participants performed 3 min of self‐paced lumbar extension on a resistance exercise machine (Nautilus Evo) which allows for isolation of the lumbar extensors through stabilization of the pelvis and has been previously shown to elicit measurable hemodynamic and metabolic responses in the paraspinal muscle in individuals with and without back pain 24,25 . Exercise intensity was normalized to 50% of the participant's body weight, and participants were instructed to pace themselves to achieve a rate of perceived exertion (RPE) of 6–7 out of 10 on the modified Borg Scale of Perceived Exertion.…”
Section: Methodsmentioning
confidence: 99%
“…The increased magnetic resonance imaging (MRI) field strength and related technological innovations have recently led to a steady growth in IVIM analysis research. IVIM analysis is used to study human physiological and pathological processes, including the differentiation of benign and malignant tumors, pathological grading of malignant tumors, prognosis prediction, and many other aspects[ 3 - 6 ]. Moreover, research on IVIM sequence application in pancreatic diseases has also increased.…”
Section: Introductionmentioning
confidence: 99%